Comparing an Apple with a Pear? The Australian Immunity Program and the Chinese Leniency Program - Jinheng Feng; Xiaomin Fang; Vai Io Lo (Bond Law Review)
The US introduced the cartel leniency program in 1978. In the past two decades, there has been a surge in the implementation of leniency programs in more than sixty jurisdictions. Although there have been numerous scholarly discussions to support the cartel leniency program, inconsistent views exist among different jurisdictions and stakeholders as to the effectiveness of the leniency program in practice. In evaluating new leniency programs, scholars and commentators have typically referred to the US and the EU models as benchmarks, but little attention has been paid to the question of whether it is desirable to apply these models in designing various leniency programs in different jurisdictions and societies. Given that Australia has recently revised its cartel immunity program for the third time, and that China’s competition authorities have proactively relied on the leniency concept to combat cartels in the past few years and are currently drafting a guideline for more effective implementation of the cartel leniency program, the time is now ripe for an apple-versus-pear comparison of these two immunity/leniency programs so as to provide more insights into the different institutional designs of immunity/leniency programs.